Hubungan Paritas dengan Kejadian Kekurangan Energi Kronik (KEK) pada Ibu Hamil Di BPM Ny. “A” Desa Gombang Kecamatan Slahung Kabupaten Ponorogo. - Sumini Sumini (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2018)
There are several factors that occur Chronic Energy Deficiency incident (CED),one of them is parity. Based on preliminary data generated from pregnant women's visitbook in January - December 2016 at BPM Mrs.